Bibliometric Analysis and Research Trends on Creative Accounting from 2000 to 2023 - Judijanto, Loso (Westscience Press, 2024)
This study employs a comprehensive bibliometric analysis to explore the extensive landscape of creative accounting research from 1958 to 2024. By analyzing thematic clusters, research trends over specific years, potential research topics in less explored areas, and patterns of author collaboration, the study provides a multidimensional view of the field's evolution and current state. Thematic analysis reveals core areas such as policy, earnings management, and the role of external audits, illustrating their interconnectedness within the research community. Temporal trend analysis identifies shifts from regulatory and ethical discussions to more complex issues like technology’s impact on creative accounting practices. Emerging research topics suggest future areas of study, including the influence of cultural perceptions and technological advancements on creative accounting. Furthermore, the author collaboration network highlights influential researchers and suggests robust collaborative ties within the community, offering insights into the social structure of academic collaboration. This study maps the development of creative accounting research, providing a foundation for future academic inquiry and practical application in the field.